Opportunities and delimitations of “Online on Demand Home Services marketplace” in Dhaka, Bangladesh - Zaman, Raisa Tasneem (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.